Deep hole plate film sealing device - ZHANG TAISONG (2014)
The utility model discloses a deep hole plate film sealing device which is used for the field of medical detection. The deep hole plate film sealing device comprises a bracket; the upper part of the bracket is provided with a film sealing hot plate which is fixedly connected with the bracket; a working platform is arranged under the bracket; the working platform is movably connected with the bracket; a pushing device is arranged under the working platform; the pushing device is fixedly connected with the bracket; a cushion is arranged above the working platform; the cushion is fixedly connected with the working platform. The cushion is added above the working platform, and the defects of a deep hole plate manufacturing technology are overcome by the cushion, so that the upper surface is maintained to be horizontal, the film sealing effect is effectively improved, and the phenomena such as leakage can be eliminated.